Perception of midwife’s profession by society - Iwanowicz-Palus, Grażyna; Golonka, Ewa; Bień, Agnieszka; Stadnicka, Grażyna (Nursing in the 21st Century, 2013)
PERCEPTION OF MIDWIFE’S PROFESSION BY SOCIETYAim. The aim of the study was an attempt to find out the opinion of the society about the profession and a role of a midwife.Materials and methods. The study was conducted in 2011 by means of the diagnostic survey method applying questionnaire technique. The research tool was a self – constructed questionnaire, which was conducted among 293 women and 212 men who live in the Lubelskie Province, Podkarpacie Province, Świętokrzyskie Province and Podlaskie Province.Results. The study showed that in women’s awareness, a midwife is a person who takes care of a woman during her whole life (33.11%), but in men’s opinion she is a person who assists a gynecologist – obstetrician (30.19%). The most important feature that a midwife should have is responsibility (women – 90.10%, men – 76.42%). A midwife has possibilities to give advice to and take care of young girls in puberty period (68.51%), women who plan pregnancy (73.66%), women who postpone the decision of pregnancy (60.99%), pregnant women (92.08%), women giving birth to a child (95.05%), women in childbirth looking after the baby (90.50%), women in menopause (53.86%), during the whole women’s life (53.57%) as well as women and their family (46.93%). Midwife’s profession in respondents’ opinion is an independent profession (53.27%).Conclusions: Midwife is a person who takes care of a woman during her whole life. The most important feature that a midwife should have is responsibility, professionalism and respect for other people. Midwife’s profession is an independent profession.